Mechanical and microstructural characterization of laser-welded joints of 6013-T4 aluminum alloy - Mota de Siqueira, Rafael Humberto; Oliveira, Aline Capella de; Riva, Rudimar; Abdalla, Antonio Jorge [UNESP]; Reis Pereira Baptista, Carlos Antonio; Fernandes de Lima, Milton Sergio (Springer, 2015)
Laser beam welding may be used in the place of the traditional riveting process for the welding of the stringers to the skin in aircrafts. This work intends to investigate the mechanical behavior of laser-welded aluminum AA6013, subjected to post-welding heating treatments (PWHT). A fiber laser with an average power of 1.5 kW was used to weld two 1.6-mm-thick sheets in T-joint configuration. After welding, the samples were separated in three groups: the first just welded, the second subjected to a PWHT during 4 h at 190 degrees C and the third during 2 h at 205 degrees C. Hoop tensile tests showed that the thermal treatment at 190 degrees C for 4 h increased the tensile strength in 76 MPa, but the strain had decreased 4 %; the thermal treatment at 205 degrees C for 2 h increased maximum strength in 65 MPa, with a decrease in strain of 5 %. In T-pull tensile tests, the tensile properties of as-welded and PWHT samples remained the same. Standard S-N curve showed that the welding reduce the number of cycles to failure for the tested stairs. PWHT did not affect fatigue properties.
Keywords: Laser beam welding; Post-welding heat treatments; Aluminum alloys; Mechanical properties